The development of the English-type passive in Balinese - Nomoto, Hiroki (UI Scholars Hub, 2018)
The morpheme -a in Balinese is ambiguous because it can serve as a third person enclitic pronoun or a passive voice marker. Various views exist about whether the morpheme can be a pronoun in the presence of a teken agentive phrase. This paper argues that it can and that the construction in which the pronoun -a and a teken phrase co-occur (the hybrid type) is an instance of clitic doubling. A hypothesis about how the third person pronoun became a passive marker and how various passive sub-types came into existence is proposed. It is claimed that the hybrid type played a key role in the change. The hybrid type supports the analysis of passives in general as a clitic doubling construction (Baker, Johnson, and Roberts 1989). A clitic doubling analysis of passives enables a new typology of passives in which passives are classified according to how the clitic and its double in a passive clause are expressed.